STRATEGI MARKETING 4.0 PADA PASCA PANEN IKAN LELE DI DESA CURUG KECAMATAN GUNUNG SINDUR KABUPATEN BOGOR - Nining Latianingsih; Dewi Winarni Suyanti; Nunung Martina; Iis Mariam (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
Community Service Program, especially the Appropriate Technology Application Program (PPTTG) in the village of Curug, Gunung Sindur District, Bogor Regency, which involves the community, especially catfish farmers, in an effort to increase community economic empowerment and marketing of catfish farming crops. Since the occurrence of Covid-19 has become a problem and has had an impact on the business activities of catfish farmers in marketing the catfish harvest because the amount of catfish consumption needs has decreased due to the decreasing purchasing power of the people around the village of Curug, the price of catfish feed has tended to rise so this condition has add to the burden of new problems for the community. PPTTG program help catfish farmers in  village  Curug as partners to be able to market their catfish harvest through direct sales and digital (online) marketing so that economic income increases and is able to buy catfish feed at a reasonable price, provide training and business assistance. catfish. The solutions offered in dealing with partner problems in developing catfish marketing through websites and internet marketing 4.0, making dumplings from catfish, help establish a special cooperative for catfish farmers so that catfish farmers have a formal organization that can assist in capitalizing catfish farmer members, providing tools for catfish production. The results of the PPTTG are the establishment of cooperatives for catfish farmers, diversifying catfish products such as dumplings, online marketing of catfish (marketing strategy 4.0), and owning the copyright and production brand rights so that catfish farmers can run catfish farming more increased. As for the sustainability of this program, it is hoped that catfish farmers in the village of Curug can continue to maintain the potential of catfish business and increase economic income